MENAKAR MINAT MASYARAKAT MENGADOPSI APLIKASI CUSTOMER SELF SERVICE BERBASIS MOBILE - Agus Gunadi; Gede Sri Darma (Faculty of Economics and Business, Universitas Warmadewa, 2022)
Modern companies are now trying to keep up with digital technology developments, focusing on optimizing processes and accelerating workflows to make them more efficient. PLN as a company that serves as a provider of electricity for the public interest has also adapted by launching a customer self service application called PLN Mobile. Currently, there are around 80 million PLN customers, but 8 million have adopted the new PLN Mobile application. This study explores the aspects that influence public interest in adopting the PLN Mobile application in Indonesia. Online-based questionnaires were distributed using Google Forms. A total of 612 responses were taken and analyzed using the SEM technique (SmartPLS 3.3.3.). This study found that: 1) Usefulness has no significant effect on Behavioral Intention. 2. Ease of Use has a significant effect on Behavioral Intention. 3. Performance Expectancy has a significant effect on Behavioral Intention. 4. Social Influence has a significant effect on Behavioral Intention. 5. Facilitating Condition has a significant effect on Use Behavior. 6. Behavioral Intention has a significant effect on Use Behavior. In conclusion, PLN is advised to focus on improving the usability of the PLN Mobile application, moreover, there are lots of substitution applications that can be used to pay electricity bills and provide attractive rewards and promotion.